Peripheral muscle fractional tissue oxygen extraction in stable term and preterm neonates during the first 24 h after birth - Wolfsberger, Christina H.; Höller, Nina; Baik-Schneditz, Nariae; Schwaberger, Bernhard; Suppan, Ena; Mileder, Lukas; Avian, Alexander; Urlesberger, Berndt; Pichler, Gerhard (Frontiers in Pediatrics, 2023)
Background Peripheral-muscle fractional tissue oxygen extraction (pFTOE) represents the relative extraction of oxygen from the arterial to venous compartment, providing information about dynamic changes of oxygen delivery and oxygen consumption. The aim of the present study was to establish reference values of pFTOE during the first 24 hours after birth in stable term and late preterm neonates. Methods The present study is a post-hoc analysis of secondary outcome parameters of prospective observational studies. Only stable neonates without infection, asphyxia and any medical support were eligible for our analysis to obtain normal values. For measurements of peripheral muscle tissue oxygenation index (pTOI) during the first 24 hours after birth in term and preterm neonates, the NIRO200/NIRO200NX was used. Arterial oxygen saturation (SpO2) was obtained by pulse oximetry. pFTOE was calculated out of pTOI and SpO2: pFTOE=(SpO2-pTOI)/SpO2. Measurements of neonates were stratified into four groups according to their respective measurement time point (6-h periods) after birth. Term and preterm neonates were analyzed separately. Mean values of measurements during the first time period (0-6h after birth) were compared to measurements of the following time periods (second=7-12h, third=13-18h, fourth=19-24h after birth). Results Two-hundred-fourty neonates (55 term and 185 late preterm neonates) had at least one peripheral muscle NIRS measurements within the first 24 hours after birth. Mean gestational age and birth weight were 39.4±1.1 weeks and 3360 (2860-3680)g in term neonates and 34.0±1.4 weeks and 2060 (1750-2350)g in preterm neonates, respectively. In term neonates pFTOE was 0.264 (0.229-0.300), 0.228 (0.192-0.264), 0.237 (0.200-0.274) and 0.220 (0.186-0.254) in the first, second, third and fourth time period. In preterm neonates pFTOE was 0.229 (0.213-0.246), 0.225 (0.209-0.240), 0.226 (0.210-0.242) and 0.238 (0.222-0.255) in the first, second, third and fourth time period. pFTOE did not show any significant changes between the time periods, neither in term nor in preterm neonates. Conclusion We provide reference values of pFTOE for stable term and preterm neonates within the first 24 hours after birth, which were stable when comparing four 6-h periods. These normal values are of great need for interpreting pFTOE in scientific context as well as for potential future clinical applications.